Study to assess the effect of mini-dose Succinylcholine for ease of laryngeal mask airway insertion - Tajne, Megha P.; Pahuja, Heena D.; Rathi, Lalit K.; Bhatnagar, Aditi; Belokar, Amitkumar H. (International Journal of Research in Medical Sciences, 2019)
Background: Propofol as sole induction agent is often insufficient for the laryngeal mask airway insertion and higher doses are at times required. The present study proposes to assess the effectiveness of 0.25mg/kg mini dose succinylcholine towards facilitation of laryngeal mask airway (LMA) insertion. Methods: In a single blinded randomized controlled trial, 68 patients posted for elective general and orthopaedic surgery were equally assigned to two groups during LMA insertion: Group S (Study group)- patients received a bolus of succinylcholine 0.25mg/kg diluted in 2 ml of 0.9% sodium chloride. Group C (Control group)-patients received a bolus dose of 2 ml of 0.9% sodium chloride. The number of attempts required and ease of LMA insertion, hemodynamic parameters and adverse responses were noted and compared between the groups. Results: The LMA was inserted in first attempt in 32 (94.11%) patients in group S and in 24 (70.58%) patients in group C. The control group had 67.62% grade 1, 32.38% grade 2 and 0% grade 3, while succinylcholine group had 73.53% grade 1, 26.47% grade 2 and 0% grade 3. Hemodynamic parameters didn’t differ significantly between the two groups at any point, but significant difference was observed between occurrence of fasciculation, head and limb movements, sore throat and coughing. Conclusions: Succinylcholine does seem to help in insertion of the laryngeal mask airway but the results could not gain the level of statistical significance, partly attributed to small sample size.